Brillouin/Erbium fiber laser with pre-amplified Brillouin pump using ring-cavity configuration - Md Samsuri, Norhakimah; Zamzuri, Abdul Kadir; Mahdi, Mohd Adzir (IEEE, 2007)
A Brillouin/Erbium fiber laser using a ring laser configuration with a pre-amplified Brillouin pump is demonstrated. This configuration generated 7 Brillouin Stokes with 0.086nm spacing and the first-Stokes peak power is at 5.638dBm.